Empowering Coastal Communities Through Ecotourism Development - Arfriani Maifizar; Sarah Natasya; Dessy Angriani (Jurnal Masyarakat Maritim, 2025)
This study explores the empowerment of coastal communities through the development of ecotourism as a sustainable approach to improving local livelihoods and environmental stewardship. The research aims to analyze how ecotourism initiatives can strengthen community participation, preserve coastal ecosystems, and diversify income sources in rural maritime areas. Using a qualitative descriptive method, data were collected through interviews, focus group discussions, and observations involving local residents, tourism managers, and government representatives. The findings indicate that ecotourism development in coastal areas creates multiple benefits—economic empowerment through local entrepreneurship, social empowerment through participatory decision-making, and environmental empowerment through conservation-based practices. Community involvement in planning and managing ecotourism activities fosters a sense of ownership and responsibility toward natural resources. Moreover, ecotourism has encouraged the revival of local culture, traditional fishing practices, and coastal heritage as valuable tourism assets. However, challenges remain, including limited infrastructure, lack of marketing capacity, and inconsistent policy support. The study concludes that empowering coastal communities through ecotourism requires an integrated approach that combines environmental sustainability, economic innovation, and social inclusivity. Strengthening institutional collaboration, capacity building, and community-based governance is essential to ensure that ecotourism not only serves as a source of income but also as a pathway for long-term coastal resilience and cultural preservation.